Association Between Frequent Use of Makeup and Presence of Depressive Symptoms-Population-Based Observational Study, Including 2400 Participants - Marcos C. Veçoso; Edileia Bagatin; Fernando L. A. Fonseca; Newton Andreo-Filho; Patrícia S. Lopes; Vânia R. Leite-Silva (Adis, Springer Healthcare, 2023)
Abstract Introduction The increased prevalence of depression is a global phenomenon, with an estimated 320 million cases worldwide. In Brazil, the World Health Organization (WHO) estimated that there are about 12 million cases or more, mainly among adult women with lower socioeconomic status, leading to a high consumption of health resources. Studies suggest a positive association of measures related to appearance care on depressive symptoms, but usually with no objective methodology. This study aimed to estimate the prevalence of depressive symptoms in adult Brazilian women with lower purchasing power and to verify the association between the intensity of symptoms and the use of makeup. Methods A national sample of 2400 cases from all regions of the country, drawn randomly from an online panel representative of the Brazilian population, was studied using an online questionnaire accessible via computer or smartphone, from which the frequency of use of makeup was surveyed, and the Zung Depressive Self-Rating Scale was applied for the inventory of symptoms. Results A prevalence of 61.4% (0.59-0.63) of depressive symptoms was identified. The association between frequent use of makeup and a lower prevalence of cases with a Zung index suggestive of mild depression was confirmed. Association between frequent use of makeup and lower intensity of depressive symptoms was also identified among cases with a Zung index suggestive of absence of depression. Additionally, an association was identified between the habit of frequent use of makeup and higher economic class as well as the younger age group. Conclusion The results suggest the hypothesis that use of makeup may contribute both to a lower prevalence of mild depression and less expressive symptoms when index of absence of depression is observed.